Respuesta :
Answer:
x = 6
Step-by-step explanation:
When we find the average, we need to add up all the values and divide the answer by the number of values.
We can use this idea as a formula to answer the question:
(4x + 3x + 12) /3 = 18
collect like terms:
(7x + 12) / 3 = 18
Get rid of the fraction:
7x + 12 = 18 x 3 (multiply both sides by 3)
7x + 12 = 54
move x to one side:
7x = 54 - 12 (to do this we subtract 12 from both sides)
7x = 42
x = 42/7 (divide both sides by 7)
x = 6
Hope this helps,
Cate